Intensity-duration-frequency curves at the global scale - Laurent G Courty; Robert L Wilby; John K Hillier; Louise J Slater (Environmental Research Letters, 2019)
Intensity-duration-frequency (IDF) curves usefully quantify extreme precipitation over various durations and return periods for engineering design. Unfortunately, sparse, infrequent, or short observations hinder the creation of robust IDF curves in many locations. This paper presents the first global, multi-temporal (1–360 h) dataset of generalized extreme value (GEV) parameters at 31 km resolution dubbed PXR-2 (Parametrized eXtreme Rain). Using these data we generalize site-specific studies to show that that GEV parameters typically scale robustly with event duration ( r ^2  > 0.88). Thus, we propose a universal IDF formula that allows estimates of rainfall intensity for a continuous range of durations (PXR-4). This parameter scaling property opens the door to estimating sub-daily IDF from daily records. We evaluate this characteristic for selected global cities and a high-density rain gauge network in the United Kingdom. We find that intensities estimated with PXR-4 are within ±20% of PXR-2 for durations ranging between 2 and 360 h. PXR is immediately usable by earth scientists studying global precipitation extremes and a promising proof-of-concept for engineers designing infrastructure in data-scarce regions.